2022
DOI: 10.1155/2022/1854473
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Preparation of Iron Oxide and Titania‐Based Composite, Core‐Shell Populated, Nanoparticulates Material by Two‐Step LASER Ablation in Aqueous Media as Antimicrobial and Anticancer Agents

Abstract: Iron oxide and titania-based composite nanoparticles (NPs) populated with core-shell structures, as part of the mixture of the monometallic NPs, were prepared in water medium by the two-fluence LASER ablation technique by applying 30 and 60 mJ/cm2 LASER energy irradiations. The prepared monometallics, composite, and core-shell NPs structures were confirmed from the XRD, TEM, and EDX analyses, followed by the FE-SEM and UV absorptions. Optically, the NPs exhibited an increase in the energy gap from 3.27 eV to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 68 publications
3
1
0
Order By: Relevance
“…The results are similar to research work reported by Neway Belachew et al 40 . and Hasan H. Bahjat et al 38 …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results are similar to research work reported by Neway Belachew et al 40 . and Hasan H. Bahjat et al 38 …”
Section: Resultssupporting
confidence: 92%
“…However, the percentage of nanoparticles in 250 nm is very less, which may be due natural particle aggregation tendency of iron. There was evidence of both agglomerated and non‐agglomerated NP formation research work as reported by Hasan H. Bahjatet al 38 . Similar results on SEM analysis are also been reported by other workers 35 …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The in vivo data suggests that the iron oxide nanoparticle inhibits the growth of the cancer cells [47] effectively. The protein (albumin) supply for the growth of the cancer cells injected in the hatched egg yolk has been disrupted by the Fe2O3 nanoparticles effectively than the drug available commercially [48][49]. This fact evidently proves the anti-angiogenic capability of the Fe2O3 nanoparticles by the reduction in number of blood cells counted than that of the…”
Section: Anti-angiogenic Effectmentioning
confidence: 92%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%